The Role of Sirt1 in Ischemic Stroke: Pathogenesis and Therapeutic Strategies - Zhang, Jun-Fang; Zhang, Yu-Lei; Wu, Yun-Cheng (Frontiers in Neuroscience, 2018)
Silent mating type information regulation 2 homolog 1 (Sirt1), a nicotine adenine dinucleotide (NAD+)-dependent enzyme, is well-known in playing a part in longevity. Ischemic stroke is a major neurological disorder and is a leading cause of death and adult disability worldwide. Recently, many studies have focused on the role of Sirt1 in ischemic stroke. Numerous studies consider Sirt1 as a protective factor and investigate the signaling pathways involved in the process under ischemic stress. However, the answer to whether upregulation of Sirt1 improves the outcome of stroke is still a controversy. In this review, we discuss the role and mechanisms of Sirt1 in the setting of ischemic stroke.